The effects of Curcuma zedoaria oil on high blood sugar level and gingivitis - Juni Handajani; Dhinintya Hyta Narissi (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2015)
Background: Hyperglycemia is a condition when blood sugar level is higher than normal. Hyperglycemia is also one of diabetes mellitus (DM) symptoms. Hyperglycemia has a correlation with the occurrence of periodontal disease. Curcuma zedoaria oil is known to decrease concentration of serum glucose. Purpose: This study was aimed to determine the effects of Curcuma zedoaria oil on high blood sugar level and gingivitis in rats. Method: This study used twenty-five male Wistar rats, divided into two groups, namely the treatment group and the control group. In the treatment group, fifteen rats were divided into three subgroups (each of which was induced with 10 μl/ml, 30 μl/ml and 50 μl/ml of Curcuma zedoaria oil). The control group was consisted often rats, divided into two subgroups, as the positive control group (induced with 10 mg/kg of Glibenclamide) and the negative control group (induced with propylene glycol). Streptozotocin (STZ) (Naclai tesque, Kyoto Japan) with a dose of 40 mg/kg was used to create hyperglycemia condition in those rats. Gingivitis was then made by using silk ligature in those hyperglycemia rats. Silk ligature was twisted at the margin of gingiva anterior mandibular incisors for seven days. After the rats had gingivitis, Curcuma zedoaria oil, glibenclamide and propylene glycol were orally administered for seven days. Their gingivitis condition was observed, and their blood sugar level was measured before and after the induction of STZ and during the treatment. The data obtained were analyzed by using Manova. Result: There were significant differences of blood sugar levels between the treatment group before and after the administration of Curcuma zedoaria oil and the positive control group (p<0.05). Healthy gingiva was then found in the treatment group and the positive control group. Conclusion: Curcuma zedoaria oil can decrease blood sugar level and gingivitis.